Is the death penalty dying? - Sarat, Austin (Elsevier JAI, 2008)
This volume of "Studies in Law, Politics, and Society" presents a unique special issue "Is the Death Penalty Dying?." Drawing together an array of distinguished scholars from political science, criminology, sociology, and law, this volume provides a comprehensive assessment of the status of the death penalty in the United States, its past, and its trajectory for the future. Taken together, the work published in this volume exemplifies the kind exciting and innovative work now being done by legal scholars from different disciplines.This is a special issue examining the death penalty in the US. It draws together an array of distinguished scholars from political science, criminology, sociology, and law.
Keywords: Capital punishment.; Criminal law & procedure.; Penology & punishment.; Law -- Criminal Law -- General.; Political Science -- General.; elektronické knihy; electronic books